The Effectiveness of Using Realistic Mathematics Education (RME)-based Students’ Worksheet to Improve Students' Mathematical Problem-solving Skills - Anggita Manggarrani; Nafida Hetty Marhaeni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study aims to determine the effectiveness of using Realistic Mathematics Education (RME)-based Students’ Worksheets (LKPD) to improve students' mathematical problem-solving skills. This type of research is experimental research with pretest posttest control group design. The samples in this study were class X-E2 as the experimental class with 36 students and class X-E3 as the control class with 36 students. Data collection techniques using interviews, observations, and pretest and posttest assessments of students' problem-solving skills on statistics material. The hypothesis of this study is that the use of RME-based LKPD is more effective in improving students' problem-solving skills than learning without using RME-based LKPD. The results obtained from this study are the use of RME-based LKPD which contains indicators of problem-solving skills proven effective to improve students' problem-solving skills. This conclusion is obtained based on the results of statistical tests, namely the Wilcoxon Signed Rank Test where the test results from the experimental class and control class have sig. 2 tailed < 0.05, Mann-Whitney U Test which has sig. 2 tailed <0.05, and the mean difference test which shows an increase in the experimental class of 28.05 and in the control class of 11.39 which shows that learning using RME-based LKPD is more effective in improving students' problem-solving skills than learning without using RME-based LKPD.